Aplikasi Pendaftar Siswa/I Baru Berbasis Web di Sekolah Yayasan Pendidikan Mutia Rahma Menggunakan Metode Vigenere - Faiz Al Farizi; Ruly Dwi Arista; Hanna Willa Dhany (CV. Hawari, 2026)
The new student admission process involves collecting and managing prospective students’ personal data, which must be handled accurately and securely. Yayasan Pendidikan Mutia Rahma still relies on manual registration procedures, causing data accumulation, recording errors, and delays in verification. This study aims to develop a web-based new student registration application that facilitates data entry and management while ensuring data confidentiality using the Vigenere Cipher method. The research method applied is software development using the Waterfall model, which includes requirement analysis, system design, implementation, and testing stages. The application is developed using HTML, PHP, JavaScript, and MySQL as the database. The Vigenere Cipher method is implemented to encrypt sensitive registration data so that information stored and transmitted through the system is protected. The results show that the developed application is able to organize registration data more systematically, reduce recording errors, speed up the verification process, and improve data security. This application supports a more efficient and secure new student admission process at Yayasan Pendidikan Mutia Rahma.